The appeal in the new matrimonial process - MONETA, PAULO (Prawo Kanoniczne, 2017)
The motu proprio Mitis Iudex issued by Pope Francis, which has introduced a reform of the nullity of marriage causes, contains a new regulation as regards the appeal. It is not clear, however, if this new regulation should be applied to all sentences or only to those sentences that declare the nullity of marriage. The author scrutinizes the arguments in favor of the different positions and the implied consequences for the concrete execution of the ecclesiastical judgment. His conclusion is that a specific regime should be applied for each of the two sentences. It is then shown what is the preliminary check that the judicial college has to accomplish in order to verify that the appeal is not pursued with the mere intent of procrastination, by referring to the decisions adopted by the Roman Rota.